Ensino de comunicação e emissão de comportamentos preventivos de autocuidados generalizados e outros repertórios em crianças com autismo - COSTA, Juliana Ribeiro Rabelo (2024)
It is common for children and young people diagnosed with autism spectrum disorder (ASD) to present difficulties in the development of language and communication, as well as in demonstrating functional skills in daily living and other types of behavioral chains. In Applied Behavior Analysis (ABA), procedures using scripts help in establishing these repertoires in this population, since they incorporate the manipulation of visual, textual or auditory cues and their subsequent fading, favoring the demonstration of more independent performances by learners. . The present study was carried out with three children diagnosed with ASD, between 4 and 6 years old. Two experiments were defined: The first evaluated the effectiveness of the procedure of fading scripts (textual or auditory cues) to establish a repertoire of verbalizing sentences with a tact function on generalized self-care preventive behaviors (putting on a mask and maintaining its use; washing hands) and other behavioral chains (daily living skills; functional play). All children demonstrated the acquisition of these verbal skills from training and, in addition, there was the emergence of related non-verbal repertoires (performing their own routines) in probes, suggesting the establishment of a saying-doing correspondence. The objective of the second experiment would have been to evaluate the effects of training non-verbal repertoires (performing the behavioral chains from the first experiment) based on a hierarchy of cues and differential reinforcement, but this was not necessary. Therefore, the second experiment was not carried out.